(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Work on the construction of democratic - legal, civil society of social development in our country is carried out step by step. The ultimate goal of all its reforms is an indicator of the organization of decent living conditions for its citizens. That is why the upbringing of a spiritually perfectly developed person is becoming one of the most important tasks. Therefore, from the first steps, it was aimed to bring the national education system to the level of world standards. The implementation of such glorious tasks could not have been achieved without the reform of the existing system of continuing education in the country. In this article, opinions and comments will be made about what the dual education system is and its importance and role in the training of specialists.